Design and Realization of a Multi-Band, High-Gain, and High-Isolation MIMO Antenna for 5G mmWave Communications - Nabeel Alsaab; Mahmoud Shaban (Applied Sciences)
This research introduces a novel, high-performance multiple-input–multiple-output (MIMO) antenna designed to operate in allocated millimeter-wave (mmWave) 5G wireless communications. Operating in the tri-band, 28, 35, and 38 GHz, the four-port MIMO antenna possesses a compact size—measuring just 50 × 50 × 0.787 mm3 (4.67λo × 4.67λo × 0.73λo). The antenna delivers a remarkable performance, achieving peak gains of 9.6, 7.8, and 13.7 dBi in the tri-band, respectively. The realized bandwidths are 1.1, 2.2, and 3.7 GHz, at the tri-band frequencies. The antenna’s performance was significantly improved by carefully spacing the elements and employing a decoupling technique using metamaterial cells. This minimized interference between the antenna elements, resulting in efficient MIMO operation with a low envelope correlation coefficient of 0.00015 and a high diversity gain approaching 10 dB, and high isolation of 34.5, 22, and 30 dB, in the tri-band. This proposed design is confirmed with experimental measurements and offers a promising candidate for multi-band use of mmWave communication systems.